Pancreatic ascites: spontaneous rupture of the Wirsung - Praderi, Raúl (Cirugía del Uruguay, 1974)
In a pacient with a cancer of papilla, ocurred the spontaneous rupture of the Wirsung duct behind the obstacle, with apparition of a pancreatic ascites. It was treated with externa! drainage and iterative anastomosis of the fistula to the jejunum. Besides that, a cholecysto jejunostomy was done because there was an obstructive jaundice. The author comments the 1areness of these observations in literature.